Tackling The Challenge Of Opioid Use And Abuse And Treatment Of Chronic Pain Management. (28th October 2020) - Arora, K; Umar, B; Hogan, K; Winston-McPherson, G N; Copeland, J R; Varney, R; Shah, V; Totten, A
Abstract: Introduction/Objective: Deaths from opioid overdose increased 12% from 2016 to 2017. This major economic burden cost roughly 78.5 billion in the US. This steep increase in drug overdose deaths can be attributed to increased synthetic opioid abuse. To better understand and reduce opioid abuse amongst patients at Henry Ford Health System, Detroit MI, we sought to collaborate with physicians to manage prescribing, interpret test results, improve patient care, and deliver more value. Primary Aim: To create a directed pain panel for ordering and interpreting pain management drugs to help providers to better manage patients and to assess compliance from test ordering history to serve patients safely and effectively. Secondary Aim: To streamline the process of prescribing pain medications and to create a patient centered approach to treat chronic non-cancer patients who actually need opioids, to minimize the risk of abuse, diversion and addiction among patients. Methods: Plan Do Check Act (PDCA) cycles of process improvement were used to achieve our two aims. In the first cycle, a drug screen-ordering guide was developed to facilitate screening (qualitative) and confirmation (quantitative) ordering practices. As part of this, providers prescribing for chronic pain patients were advised to use drugs of abuse panel rather than our emergency drug screen. In the second cycle, a directed pain panel (DPP) was introduced with reflex to confirmation testing. The DPP led to discovery of unexpected fentanyl positives, which were further investigated. Results: A survey was conducted to investigate provider-ordering practices, which showed that use of the new drugs of abuse panel rose from 57% to 77%. The DPP was accepted by 60% of physicians and was frequently reordered in follow-up. Analysis of unexpected fentanyl positivity revealed 30% true positivity, thus identifying unknown patient use. A future PDCA cycle is focused on developing, implementing, and measuring the customer value of a laboratory generated interpretive opioid results report at 5 similar organizations with a goal to assist with test selection and simplify provider interpretation of results. Conclusion: A future PDCA cycle is focused on developing, implementing, and measuring the customer value of a laboratory generated interpretive opioid results report at 5 similar organizations with a goal to assist with test selection and simplify provider interpretation of results.